2023
DOI: 10.1111/nph.18819
|View full text |Cite
|
Sign up to set email alerts
|

A data‐intensive documentation of plant ecosystem thermoregulation across spatial and temporal scales

Abstract: This article is a Commentary on Guo et al. (2023), 238: 1004–1018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…This positive association of heat tolerance with both LA and LDM suggests that a lower boundary layer conductance in larger leaves led to higher leaf temperatures (Guo et al . 2022; Drake 2023) and resulted in higher values of T 15 , T 50 , and D 50 in coffee plants. Interestingly, our findings diverge from several studies that reported a positive association of photosynthetic heat tolerance with LMA (Sastry & Barua 2017; Li et al .…”
Section: Discussionmentioning
confidence: 99%
“…This positive association of heat tolerance with both LA and LDM suggests that a lower boundary layer conductance in larger leaves led to higher leaf temperatures (Guo et al . 2022; Drake 2023) and resulted in higher values of T 15 , T 50 , and D 50 in coffee plants. Interestingly, our findings diverge from several studies that reported a positive association of photosynthetic heat tolerance with LMA (Sastry & Barua 2017; Li et al .…”
Section: Discussionmentioning
confidence: 99%